Examining the Impact of Trade Fluctuations on the Substitution Elasticity of Selected Goods During Economic Boom - Fazeli Nahrkhalaje, Lila; Raeispour Rajabali , Ali; Zayanderody, Mohsen (Business, Marketing, and Finance Open, 2025)
The purpose of this study is to examine the effects of trade fluctuations on the substitution elasticity of selected goods during periods of economic boom. In this research, the Armington elasticity was calculated for 22 selected goods (considering statistical limitations) at the 2-digit, 3-digit, and 4-digit levels of the Standard International Industrial Classification (SIIC). The Armington elasticity essentially measures the sensitivity of the ratio of imported demand to domestic demand for a good in response to changes in the relative price of domestic versus imported goods. Therefore, in this study, using EViews 10 software and a multivariate regression model based on time series data, the Armington elasticity was initially calculated. The results indicate that this elasticity is positive and statistically significant for 16 selected goods. In the next step, using an ARDL regression model, the findings suggest that trade fluctuations have a significant impact on the substitution elasticity of selected goods. Additionally, trade fluctuations positively affect the substitution elasticity of selected goods during economic boom periods. Hence, all research hypotheses were confirmed at a 95% confidence level.